Immunological Properties of Natural Gums and Their Potential as Adjuvant of Vaccines - Mahyar Dadbin; Mohammad Soltanpour; Laleh Khodaie* (Research Journal of Pharmacognosy, 2025)
Vaccinations can effectively prevent infectious ailments. Adjuvants, whether chemical or natural, play a pivotal role in enhancing vaccine efficacy. There has been a recent surge in interest in natural adjuvants, particularly due to their biological compatibility and safety. Natural gums, with immune-enhancing properties, could be used as safe adjuvants. Thus, this study aimed to investigate gums' various properties and potential as adjuvants. In this systematic review, data were obtained from scientific databases, such as Scopus, Web of Science (WOS), Embase, PubMed, and Google Scholar. Various keywords were used: carbohydrate, herb, gum, adjuvant, vaccine, and polysaccharide. The criteria for inclusion and exclusion, and the quality assessment of the included studies, resulted in the creation of a flowchart for the search strategy. Commonly used natural gums with the potential to be used as adjuvant, their sources, components, and various properties were tabulated. The immunological action of gums was also investigated. Among the commonly used gums, only xanthan was previously investigated as an immune potentiate. Moreover, toxicity, safety, limitations, challenges, and future perspectives regarding gum-based adjuvants were discussed. The results suggest that natural gums could be used solely or in combination with other synthetic and natural adjuvants due to potentiating immunological activities and protection of vaccine antigens from degradation. Further preclinical and clinical studies are required to confirm their potential and efficacy.